2017
DOI: 10.1098/rsos.170103
|View full text |Cite
|
Sign up to set email alerts
|

A frequency quantum interpretation of the surface renewal model of mass transfer

Abstract: The surface of a turbulent liquid is visualized as consisting of a large number of chaotic eddies or liquid elements. Assuming that surface elements of a particular age have renewal frequencies that are integral multiples of a fundamental frequency quantum, and further assuming that the renewal frequency distribution is of the Boltzmann type, performing a population balance for these elements leads to the Danckwerts surface age distribution. The basic quantum is what has been traditionally called the rate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Using equations (A.8) and (A.15) in the appendix (i.e. electronic supplementary material, S1) of the manuscript of Mondal & Chatterjee [ 29 ] and generalizing them to unsteady-state conditions yields the fundamental differential equation that describes the unsteady-state GD age distribution function f ( t , t p ): 0 where t is the age of a surface element and t p is the time elapsed since the commencement of the mass or heat transfer process (i.e. the process or ‘clock’ time).…”
Section: Unsteady-state Gd Age Distributionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using equations (A.8) and (A.15) in the appendix (i.e. electronic supplementary material, S1) of the manuscript of Mondal & Chatterjee [ 29 ] and generalizing them to unsteady-state conditions yields the fundamental differential equation that describes the unsteady-state GD age distribution function f ( t , t p ): 0 where t is the age of a surface element and t p is the time elapsed since the commencement of the mass or heat transfer process (i.e. the process or ‘clock’ time).…”
Section: Unsteady-state Gd Age Distributionmentioning
confidence: 99%
“…Recently, Mondal & Chatterjee [ 29 ] have given a deeper theoretical understanding of the Danckwerts surface renewal model by invoking the concept of a frequency quantum, which is analogous to the energy quantum postulate which Planck used to derive his famous formula for the energy density of black-body radiation. By assuming that surface elements of a particular age have renewal frequencies that are integral multiples of this fundamental frequency quantum, and by further assuming a Boltzmann-type distribution for the renewal frequency, they showed that a population balance for these elements led to the Danckwerts surface age distribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations